Blood and body fluids: knowledge, attitude and practice of medical students in Ajman, UAE (International Journal of Occupational Safety and Health, 2013)
The health care workers should be aware of Universal Work Precaution (UWP) as there is an increased risk of exposure to infectious diseases which is considered mainly due to accidental exposure to blood and body fluids. This study mainly aims to evaluate the knowledge, attitude and practice of medical students on blood and body fluids at Gulf Medical University, Ajman, United Arab Emirates (UAE). The study subjects constituted 212 medical students of academic years 2005 – 2009. A self administered questionnaire was utilized for data collection and analysis was performed using statistical software PASW 17. Results: The participant’s age ranged from 17 to 27 years. A statistically significant association (P